2018
DOI: 10.1038/s41565-018-0089-z
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic interaction between neighbouring platinum monomers in CO2 hydrogenation

Abstract: Exploring the interaction between two neighbouring monomers has great potential to significantly raise the performance and deepen the mechanistic understanding of heterogeneous catalysis. Herein, we demonstrate that the synergetic interaction between neighbouring Pt monomers on MoS greatly enhanced the CO hydrogenation catalytic activity and reduced the activation energy relative to isolated monomers. Neighbouring Pt monomers were achieved by increasing the Pt mass loading up to 7.5% while maintaining the atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
498
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 640 publications
(505 citation statements)
references
References 39 publications
5
498
1
1
Order By: Relevance
“…According to the criteria that the optical intensity of each atom in the HAADF‐STEM image is positively correlated with its atomic number, the Ru atom should be brighter than the Mo and S atoms . As expected, the Ru is single‐atomically embedded in the plane of the 2D MoS 2 , as shown in Figure e,g, where these bright spots are unambiguously assigned to the Ru atom . Moreover, the enlarged regions (Figure f,h) further reveal that single Ru atoms precisely occupy the sites of the Mo atoms in the lattice arrangement.…”
Section: Resultsmentioning
confidence: 99%
“…According to the criteria that the optical intensity of each atom in the HAADF‐STEM image is positively correlated with its atomic number, the Ru atom should be brighter than the Mo and S atoms . As expected, the Ru is single‐atomically embedded in the plane of the 2D MoS 2 , as shown in Figure e,g, where these bright spots are unambiguously assigned to the Ru atom . Moreover, the enlarged regions (Figure f,h) further reveal that single Ru atoms precisely occupy the sites of the Mo atoms in the lattice arrangement.…”
Section: Resultsmentioning
confidence: 99%
“…Ag, Au, Pt and their alloys are commonly used as catalysts for CO 2 reduction. Li et al reported a SAC which consisted of neighboring Pt monomer on MoS 2 with mass loading up to 7.5 wt%. This catalyst exhibited the synergetic interaction between neighboring Pt monomers and conversion of CO 2 into methanol and formic acid.…”
Section: Recent Advances Of Densely Populated Sacs In Catalytic Applimentioning
confidence: 99%
“…For example, Nb/Re substituting W in WSe 2 can induce p/n‐type doping with long‐term stability compared with doping by molecule adsorption on the surface. Moreover, the substitutional metal atoms can activate the basal plane of MX2 by acting as single‐atom catalysts for a variety of reactions . Furthermore, incorporation of magnetic metal elements (e.g., Ni, Co) can introduce magnetism into nonmagnetic MX 2 , which may be useful for spintronics.…”
mentioning
confidence: 99%